ATYPICAL HEMOLYTIC-UREMIC SYNDROME IN THE FEMALE PATIENT WITH CONCURRENT MENOMETRORRHAGIA (clinical case) - A. V. Pyregov; T. A. Fedorova; A. Yu. Korolev; K. I. Grischuk (Вестник анестезиологии и реаниматологии, 2018)
The article describes the follow-up over the development of atypical hemolytic-uremic syndrome in the female patient suffering menometrorrhagia which manifested with concurrent metrorrhagia and was accompanied with acute renal failure.